Cattle drinking water quality in the cow-calf beef operation in southern Chihuahua, Mexico - Saucedo-Terán, Rubén Alfonso; SAUCEDO TERÁN, RUBEN ALFONSO; Holguín- Licón, Celia; Jurado-Guerra, Pedro; Ochoa-Rivero, Jesús Manuel; Rubio-Arias, Héctor Osvaldo (Ecosistemas y Recursos Agropecuarios, 2017)
Despite the key role of water in livestock growth and reproduction, there is little information on water quality for Mexico s beef cattle ranches. The objective of this study was to evaluate drinking water quality for beef cattle in the cow-calf operation through calculation of a water quality index (WQI) that relates water physical-chemical composition with common cattle drinking water sources. The study was conducted in 25 cattle ranches of the cow-calf system in seven municipalities of Chihuahua, Mexico. In all cattle ranches, water samples were collected from the main water sources, and physical and chemical parameters were analyzed. Statistical analyses were done through Kruskal-Wallis test, considering water sources (WS) as a source of variation. The WQI was calculated considering the parameters closely related to animal health and productivity and following standard procedures. Most parameters showed high variation among WS. The only parameters in uenced by WS were pH, As (p < 0.05) and Co (p < 0.01). The parameters that surpassed the optimum level for cattle drinking were turbidity for all WS and Mn for earthen tank and spring/river water. Groundwater showed the best quality with a 50.34 WQI, corresponding to good class. Earthen tank water also corresponded to good class with a 98.8 WQI, while spring/river water was classi ed as poor water for cattle with a 114.47 WQI.